2015
DOI: 10.1108/ijm-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Migration, human capital and social capital: lessons for the EU neighbouring countries

Abstract: Purpose:The European Union and its European Neighbourhood are mutually dependent. In the next decades, the European Union (EU) will need to import foreign labour in response to different challenges. The geographical proximity, economic, cultural and historical links with EU Neighbouring countries make them an important potential source of labour force and, moreover, they are the main countries of origin and transit of legal and illegal migration towards Europe. The purpose of this special issue is to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Our study demonstrates that social protection can weaken the relationship between social capital and poverty level. Consistent with the previous studies (Beenstock et al, 2015;Chan and Wong, 2020;Wang, 2021), this result highlights the importance of public policy in reducing inequality. For migrant workers in China, the household registration system, informal work, and prejudice from local people limit their children's rights in education, social security and medical services (Wang, 2021).…”
Section: The Role Of Social Protection Between Social Capital and Pov...supporting
confidence: 91%
See 2 more Smart Citations
“…Our study demonstrates that social protection can weaken the relationship between social capital and poverty level. Consistent with the previous studies (Beenstock et al, 2015;Chan and Wong, 2020;Wang, 2021), this result highlights the importance of public policy in reducing inequality. For migrant workers in China, the household registration system, informal work, and prejudice from local people limit their children's rights in education, social security and medical services (Wang, 2021).…”
Section: The Role Of Social Protection Between Social Capital and Pov...supporting
confidence: 91%
“…Public or formal social protection can empower people to reduce vulnerability, risk, and economic shocks at the macro level (Devereux and Getu, 2016). Previous studies have found that individuals have the higher social capital to get out of poverty if they can access social protection, such as education (or professional training) (Pillai et al, 2021;Rea et al, 2013), health and safety protection (Moyce and Schenker, 2018) and unemployment bene ts (Beenstock et al, 2015;Wang, 2021). For example, Osabohien et al (2020) found that social protection, such as building human resources and equality of public resources, is a vital strategy to reduce poverty and inequality in Africa.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to suppose, indeed, that if immigrants (emigrants) end up working in the sector in which the country of origin (destination) has comparative advantage, it is more likely for them to channel the information to the destination (origin) country about this comparative advantage. Besides, we would like to measure the knowledge transmission channel by considering the skill level of migrants following previous studies (Beenstock et al , 2015; Giovannetti and Lanati, 2017; Giovannetti et al , 2019). Both improvements can only be realized by adopting other data sources as in our data from UN we only have international migrant stock by age, sex and origin.…”
Section: Discussionmentioning
confidence: 99%
“…From a different perspective, several key findings and overall policy conclusions from the SEARCH project were geared to a non-scientific policy-oriented readership (Sinozic et al 2015). Focusing their special issue on human capital, migration and social capital, Beenstock et al (2015) stress the importance of ENCs as a key source of future labour force and economic growth in the European Union. The traditional channels of integration (trade and FDI) comprise another special issue that stresses the importance of collateral developments in governance, quality of institutions, human capital and technological upgrading to truly deepen economic and trade relations among neighbours (Crescenzi and Petrakos 2016).…”
mentioning
confidence: 99%